2017
DOI: 10.1001/jamainternmed.2017.2924
|View full text |Cite
|
Sign up to set email alerts
|

Injurious Falls and Syncope in Older Community-Dwelling Adults Meeting Inclusion Criteria for SPRINT

Abstract: Role of the Funder/Sponsor: The funding sources had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…), most NH residents and geriatrics patients have greater disease and function burden, higher fall rates, and worse survival than that study's subjects (Sexton et al. ). Since hypertension is the most common chronic condition among NH residents in the United States, with 54 percent of all residents affected (Simonson, Han, and Davidson ), the potential impact of new evidence is great.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…), most NH residents and geriatrics patients have greater disease and function burden, higher fall rates, and worse survival than that study's subjects (Sexton et al. ). Since hypertension is the most common chronic condition among NH residents in the United States, with 54 percent of all residents affected (Simonson, Han, and Davidson ), the potential impact of new evidence is great.…”
Section: Discussionmentioning
confidence: 89%
“…; Sexton et al. ; Williamson et al. ), with such harms leading to higher long‐term mortality risk (Benetos et al.…”
mentioning
confidence: 99%
“…However, the external validity of this finding is questionable. A nationally representative longitudinal study of older adults meeting the SPRINT inclusion criteria observed a fivefold higher rate of injurious falls than the standard care group within SPRINT during a comparable follow-up period 49. Furthermore, it is apparent that medication adherence of clinical trial participants is higher.…”
Section: Discussionmentioning
confidence: 99%
“…57 It has been proposed that injurious falls and syncope incidence may have been underreported in interventional studies such as SPRINT. 58 In this context, bedtime administration of antihypertensive treatment, addressing both supine hypertension and an increased risk of BP fall during morning hours, seems to be less harmful, more optimal in reducing CV risk, and might be a standard approach in the future. 59 Finally, it is important to acknowledge that the identification of any optimum SBP therapeutic goal must Together with increased arterial stiffness, LVH is likely to be responsible for the impaired diastolic function in patients with OH.…”
Section: Cardiovascular Risk Factors and Circulatory Compli-mentioning
confidence: 99%